Coordination‐Induced Assembly of Intelligent Polysaccharide‐Based Phototherapeutic Nanoparticles for Cancer Treatment. Issue 24 (18th November 2016) - Tian, Ye; Guo, Ranran; Wang, Yajun; Yang, Wuli
Abstract : Smart polysaccharide‐based anticancer phototherapeutic nanoparticles are prepared via a coordination‐induced assembly process. Upon irradiated with a near infrared laser, the nanoparticles are not only able to simultaneously generate reactive oxygen species and hyperthermia that ablate tumors, but also possess tumor microenvironment‐responsive off/on near infrared fluorescence and enhancement in photothermal effect, making them promising theranostic platform of cancer.